As tramas do agronegócio nas terras do Sudeste Goiano - Matos, Patrícia Francisca de (2011)
The present thesis aims to understand the socio-spatial trams of the agribusiness in the Southeast of Goiás. To achieve the objectives proposed, the methodology used was qualitative approach with a theoretical review, field research and data collects in primary and secondary sources. The time frame defined the period after 1980, marked by the territorialization of the modern agriculture, made possible by the private capital and apparatus of the State, and that it contributed for the modernization of the territory. However, they had been necessary reflections on previous periods, therefore the initial insertion of modernization of the territory in Goiás, specifically in the Southeast of Goiás if it gave for the prolongation of the Railroad Mogiana linked the Southeast to the Midwest, through the states of Goiás, in the cities of Goiandira, Catalão, Ipameri and Pires do Rio, in the first decades of twentieth century, reaching Anápolis in middle of years 1930. The Railroad promoted in Goiás, especially in the Southeast of Goiás, economic, social, cultural and politics transformations. Although the promising economic development of the beginning of twentieth century, the Southeast of Goiás entered in decay around 1940. From the 1970‟s, but especially in 1980, the Southeaste region has taken over the economic and population growth. One of the reasons for the process was the consolidation of the modernization of agriculture. The territorialization of modern agriculture in Southeast of Goiás transformed the agrarian space of many municipalities as results of the new logics that if they had installed, marked by the intense use of science and the technology, by specialization, particularly the production of grains, aimed at agribusiness and foreign markets, by territorialization of agribusinesses, at last, new forms of exploration of the land. Added to this, the concentration of the land, the environmental impacts and the replacement of traditional producers, in many cases peasants, for agribusiness entrepreneurs. Thus, the territorialization of the agribusiness, promove in the Southeast of Goiás, new uses of the territory by rural enterprises and the agricultural industries, creating new territoriality in the field and in the city.